Transversality and Alternating Projections for Nonconvex Sets - Drusvyatskiy, D.; Ioffe, A. D.; Lewis, A. S. (Foundations of computational mathematics, 2015)
We consider the method of alternating projections for finding a point in the intersection of two closed sets, possibly nonconvex. Assuming only the standard transversality condition (or a weaker version thereof), we prove local linear convergence. When the two sets are semi-algebraic and bounded, but not necessarily transversal, we nonetheless prove subsequence convergence.